Repetitively dosed docetaxel and 153samarium‐EDTMP as an antitumor strategy for metastatic castration‐resistant prostate cancer. Issue 17 (13th June 2013) - Autio, Karen A.; Pandit‐Taskar, Neeta; Carrasquillo, Jorge A.; Stephenson, Ryan D.; Slovin, Susan F.; Rathkopf, Dana E.; Hong, Christina; Heller, Glenn; Scher, Howard I.; Larson, Steven M.; Morris, Michael J.
<x xml:space="preserve">Abstract</x> BACKGROUND β‐emitting bone‐seeking radiopharmaceuticals have historically been administered for pain palliation whereas docetaxel prolongs life in patients with metastatic castration‐resistant prostate cancer (mCRPC). In combination, these agents simultaneously target the bone stroma and cancer cell to optimize antitumor effects. The toxicity and efficacy when each agent is combined at full, recommended doses, in a repetitive fashion is not well established. METHODS Patients with progressive mCRPC and ≥3 bone lesions received 153Sm‐EDTMP (samarium‐153 ethylene diamine tetramethylene phosphonate) at a dose of 1.0 mCi/kg every 9 weeks and docetaxel at a dose of 75 mg/m2 every 3 weeks. In the absence of unacceptable toxicity, patients were allowed to continue additional cycles, defined by 9 weeks of treatment, until intolerance or biochemical/radiographic disease progression. RESULTS Of the 30 patients treated, approximately 50% were considered to be taxane‐naive, 36.7% were taxane‐refractory, and 13.3% had previously been exposed to taxanes but were not considered refractory. Patients received on average 2.5 cycles of treatment (6.5 doses of docetaxel and 2.5 doses of 153Sm‐EDTMP). Twelve patients (40%) demonstrated a decline in their prostate‐specific antigen level of ≥50%. The median progression‐free survival (biochemical or radiographic) was 7.0 months and the overall survival was 14.3 months. Nine patients (30%) did not recover platelet counts >100 K/mm3 after a median of 3 cycles to allow for additional treatment, with 4 patients experiencing prolonged thrombocytopenia. The most common reasons for trial discontinuation were progressive disease and hematologic toxicity. CONCLUSIONS The results of the current study indicate that 153Sm‐EDTMP can be safely combined with docetaxel at full doses on an ongoing basis in patients with mCRPC. Although thrombocytopenia limited therapy for some patients, preliminary efficacy supports the strategy of combining a radiopharmaceutical with chemotherapy, which is an appealing strategy given the anticipated availability of α emitters that can prolong survival. Cancer 2013;119:3186–3194. © 2013 American Cancer Society.